2020
DOI: 10.1111/opo.12671
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of microglia and monocytes to the development and progression of age related macular degeneration

Abstract: Purpose Age related macular degeneration (AMD) is the leading cause of irreversible vision loss in industrialised nations. Based on genetics, as well as proteome analysis of drusen, the role the innate immune system in the development and/or progression of the disease is well established. Mononuclear phagocytes, such as microglia and monocytes, play critical roles in innate immunity. Here, the role of retinal microglia in mediating normal retinal function, and how these cells change with age is discussed, so a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 84 publications
(222 reference statements)
0
31
0
1
Order By: Relevance
“…A hallmark of AMD development is the recruitment of the innate immune cells in the subretinal area with age [95]. The resident immune cells are the microglia in the retina, similar to tissue macrophages, which maintain normal retinal function, including the monitor and phagocytosis of damaged cell components [96].…”
Section: Microglia/macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…A hallmark of AMD development is the recruitment of the innate immune cells in the subretinal area with age [95]. The resident immune cells are the microglia in the retina, similar to tissue macrophages, which maintain normal retinal function, including the monitor and phagocytosis of damaged cell components [96].…”
Section: Microglia/macrophagesmentioning
confidence: 99%
“…The resident immune cells are the microglia in the retina, similar to tissue macrophages, which maintain normal retinal function, including the monitor and phagocytosis of damaged cell components [96]. Senescent microglia respond slowly to the injury and microglial dysfunction is a key factor in early AMD [95]. When retinal microglia migrate to the subretinal space, they may cause obvious changes in RPE cells, including further accumulation of microglia, increasing inflammation in the outer layer of the retina, and contributing to the formation of new blood vessels in wet AMD [97].…”
Section: Microglia/macrophagesmentioning
confidence: 99%
“…Two potential mechanisms have been suggested that include action through its anti-apoptotic properties and anti-inflammatory effect (11). The innate immune system, which has a rapid non-specific response to an antigen, has been implicated in the development of retinal degeneration including human AMD and RP (12). In healthy retina, microglia are located in the outer and inner plexiform layers and survey retinal homeostasis like guardians of the retina (12).…”
Section: Introductionmentioning
confidence: 99%
“…The innate immune system, which has a rapid non-specific response to an antigen, has been implicated in the development of retinal degeneration including human AMD and RP (12). In healthy retina, microglia are located in the outer and inner plexiform layers and survey retinal homeostasis like guardians of the retina (12). However, in the stage of retinal degeneration, microglia get activated and migrate to outer retina and subretinal space, the space between the outer segments of photoreceptors and retinal pigment epithelium (RPE).…”
Section: Introductionmentioning
confidence: 99%
“…Activated microglia upregulate internalisation and lysosomal acidification for the clearance of undegraded or misfolded proteins, some of which go on to form pathognomonic plaques and amyloid-b fibrils in neurodegenerative diseases (Majumdar et al, 2007, Iribarren et al, 2005, Lai and McLaurin, 2012. Microglia are also implicated in other age-linked degenerative diseases such as age related macular degeneration (AMD) (Fletcher, 2020). Studies show that with age, microglia are less capable and slower in responding to injury but also present an increased inflammatory status that is prolonged and more difficult to resolve (Damani et al, 2011, Norden and Godbout, 2013, Von Bernhardi et al, 2015.…”
Section: Macrophages and Microglia In Innate Immunitymentioning
confidence: 99%